Home away from home - the role of social support for international students’ adjustment - Lashari, Sana Anwar (Universiti Utara Malaysia Press, 2018)
Purpose – Academic and psychological adjustment of international students is central to their success while pursuing their degrees abroad. However, acculturation stress is abundant and may pose as a challenge. Thus, in this study we examined whether social support mediates the association between acculturation stress and academic and psychological adjustment. Methodology – A cross sectional research design was employed. A total of 200 postgraduate international students from three Malaysian public universities were recruited to participate in the study. The Student Adjustment to College Questionnaire was employed to measure their academic adjustment and psychological adjustment. The Multidimensional Scale for Perceived Social Support and the Acculturative Stress Scale for International Students were used to collect data on social support and acculturation stress. Path analysis by AMOS 23 was used to test the hypothesized relationship.Findings – Results provided support for the proposed model, revealing that social support was associated with greater academic and psychological adjustment among international students. Significance – The present study has implications for university policies, counsellors, and student affairs departments on the need to take measures to facilitate healthy academic and psychological adjustment among international students.